Preserving digital materials - Harvey, D. R. (Douglas Ross), 1951- (K.G. Saur, 2005)
"Digital preservation is an issue faced by practitioners in the library and recordkeeping professions, yet most professionals have little time to keep up with the latest techniques and standards. This work provides a single-volume introduction to the principles, strategies and practices currently applied by librarians and recordkeepers to the preservation of digital information and will assist them to make informed decisions about the role of digital information in their care. This book will be essential as a professional reference tool for all librarians, recordkeepers and archivists with preservations responsibilities as well as being a definitive source of information for the whole profession including students."--Jacket.